2022
DOI: 10.3389/fcvm.2022.998842
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine booster significantly decreases the risk of intensive care unit hospitalization in heart failure patients during the Omicron variant wave: A population-based study

Abstract: BackgroundHeart failure (HF) patients are at higher risk of severe coronavirus disease 2019 (COVID-19). The Omicron variant has many novel mutations including those in the spike protein, leading to questions about vaccine effectiveness. The aim of this analysis was to evaluate the effectiveness of the COVID-19 vaccine with or without a booster (i.e., after the third dose) during the Omicron variant wave.MethodsChronic heart failure patients in the Czech Republic were included in the analysis. COVID-19 infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Additionally, for high-risk patients, such as the elderly and those with cardiovascular diseases, medication and lifestyle interventions should be used to prevent and mitigate HF. Moreover, the ndings underscore the importance of COVID-19 vaccination in reducing cardiovascular complications in HF patients, as evidenced by studies from New York City and the Czech Republic showing lower hospitalization and mortality rates among vaccinated individuals [44,45]. The application of COVID-19 vaccines is becoming increasingly widespread [46].…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Additionally, for high-risk patients, such as the elderly and those with cardiovascular diseases, medication and lifestyle interventions should be used to prevent and mitigate HF. Moreover, the ndings underscore the importance of COVID-19 vaccination in reducing cardiovascular complications in HF patients, as evidenced by studies from New York City and the Czech Republic showing lower hospitalization and mortality rates among vaccinated individuals [44,45]. The application of COVID-19 vaccines is becoming increasingly widespread [46].…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Furthermore, Remdesivir, which halved viral production, led to a lower risk of hospitalization, a shorter hospital stay, or death, with an overall reduction of infection-related detrimental cardiovascular events. Dexamethasone demonstrated to reduce mortality in critically ill COVID-19 patients, and recent data highlighted the clear reduction of in-hospital intensive care hospitalization for HF patients with a history of vaccination during the SARS-CoV-2 Omicron wave, which was more pronounced in those with a booster dose [ 18 ]. An interesting analysis from the MedStar Health system compared the clinical characteristics and outcomes in patients with myocardial injury across the COVID-19 waves.…”
Section: Difference In Cardiovascular Comorbidities Cardiovascular Co...mentioning
confidence: 99%
“…In a population-based cohort study in the Czech Republic in 2022, 9728 patients with HF who contracted COVID-19 (SARS-CoV-2) were evaluated. They found that the risk of intensive care hospitalization was 7.6% in unvaccinated patients, 4.8% in vaccinated patients and only 2.9% in patients who received a booster dose 54 .…”
Section: Role Of Covid-19 Vaccinesmentioning
confidence: 99%